Reproducibility of microhandeness measurements in different surfices - Roberto, Andiara Ribeiro [UNESP]; Borges, Carlos Henrique Braga [UNESP]; Jassé, Fernanda Ferreira [UNESP]; Boaventura, Juliana Maria Capelozza [UNESP]; Rastelli, Alessandra Nara de Souza [UNESP]; Reis, José Maurício Santos Nunes [UNESP]; Saad, José Roberto Cury [UNESP] (My University, 2012)
The aim of this study was to assess inter and intra-examiner reproducibility of Knoop hardness (KH) of two materials: composite resin (CR – FiltekTM Supreme XT- 3M ESPE) and bovine dental enamel (BDE). Five specimens were made for each material. The CR composite resin was inserted into a cylindrical metal matrix (4 x 2mm, ISO 4049) and photo-activated for 40s on the upper side (top) with a LED Celalux® (Voco, Germany). BDE specimens were taken from the buccal side of the teeth in blocks of 3x3x3mm that were embedded into acrylic discs, flattened with sandpapers and polished. Three KH readings were performed for each specimen using load of 25 gf applied for 5 seconds, at predetermined intervals: immediately and after 4 and 7 days of preparation. Each indentation was measured using a microhardness tester by three independent observers in each period of analysis. KH values were recorded separately by their respective observers. KH values were recorded separately by their respective observers. Data were statistically analyzed by ANOVA and Tukey’s test (α=0.05). To test for a possible correlation between measurements of each examiner, a linear regression analysis was performed. There was no statistical difference (P> 0.05) in intra and inter-examiner ratings, regardless of the period of analysis. A strong positive linear correlation (BDE- r(mean)=0.87; CR- r(mean)=0.90) was observed between KH measurements of the different examiners. The KH test showed high reproducibility among multiple examiners, regardless of periods or the materials used

O objetivo deste trabalho foi estimar a reprodutibilidade intra e interexaminadores das mensurações de dureza knoop (DK) de dois materiais: resina composta (RC- FiltekTM Supreme XT- 3M ESPE) e esmalte dental bovino (EDB). Cinco corpos-de-prova foram confeccionados para cada material. A RC foi inserida em matriz metálica circular (4 x 2 mm, ISO 4049) e fotoativada por 40 s na face superior com LED Celalux® (Voco, Alemanha). Para a confecção dos corpos-de-prova de EDB, blocos (3 x 3 x 3 mm) obtidos a partir da face vestibular de dentes bovinos foram incluídos em discos de acrílico, desgastados com lixa e polidos. Três leituras de DK foram realizadas com carga de 25 g durante 5 s para cada corpo-de-prova, em três tempos: imediatamente e após 4 e 7 dias da confecção. Cada indentação foi mensurada, em microdurômetro, por 3 observadores independentes, em cada período da análise. Os valores de DK foram registrados isoladamente por seus respectivos observadores. Os dados foram submetidos à ANOVA e Tukey (α=0,05). Para avaliar o coeficiente de correlação (r) entre as observações de cada examinador, uma regressão linear foi realizada. Não houve diferença estatística (P>0,05) nas avaliações intra ou inter examinador, independentemente do período de análise. Observou-se forte correlação (EDB- r(médio)=0,87; RC- r(médio)=0,90) entre as mensurações de DK dos diferentes examinadores. O teste de DK apresentou elevada reprodutibilidade entre os múltiplos examinadores, independentemente dos períodos ou dos materiais utilizados.
Reprodutibilidade de mensurações de microdureza em diferentes superfícies
Keywords: Reproducibility of results; Hardness tests; Dentistry; Reprodutibilidade dos testes; Testes de dureza; Odontologia